2016
DOI: 10.1007/s13197-016-2448-9
|View full text |Cite
|
Sign up to set email alerts
|

Defatted coconut residue crude polysaccharides as potential prebiotics: study of their effects on proliferation and acidifying activity of probiotics in vitro

Abstract: This paper reports on the extraction, partial characterization and the potential application of crude polysaccharides from defatted coconut residue as a prebiotic. The coconut residue was defatted and extracted to obtain the crude polysaccharides and its physicochemical properties were determined. The crude polysaccharides were assessed for monosaccharide composition, total carbohydrate content, reducing sugar concentration and protein content determination. The functional group and structural elucidation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The results indicated that the acidifying activity of the Lactobacillus brevis varied depending on the strain of the bacteria. Similar results were obtained by Abbasiliasi et al [37], who confirmed that the acidifying activity of Lactobacillus bulgaricus and Lactobacillus casei varied depending on the types and concentrations of bacteria. According to Yoon et al [35], Lactobacillus plantarum and Lactobacillus delbrueckii produced significantly more titratable acidity than Lactobacillus casei.…”
Section: Discussionsupporting
confidence: 89%
“…The results indicated that the acidifying activity of the Lactobacillus brevis varied depending on the strain of the bacteria. Similar results were obtained by Abbasiliasi et al [37], who confirmed that the acidifying activity of Lactobacillus bulgaricus and Lactobacillus casei varied depending on the types and concentrations of bacteria. According to Yoon et al [35], Lactobacillus plantarum and Lactobacillus delbrueckii produced significantly more titratable acidity than Lactobacillus casei.…”
Section: Discussionsupporting
confidence: 89%
“…Most prebiotics are short-chain carbohydrates with a degree of polymerization of two or more, e.g., inulin, fructooligosaccharides, and galactooligosaccharides ( Figueroa-Gonzalez et al, 2011 ). Several studies have shown that some plant polysaccharides could be used as prebiotics, e.g., ginseng polysaccharides, Mangifera pajang fibrous polysaccharides, mushroom polysaccharides, and coconut polysaccharides ( Al-Sheraji et al, 2012 ; Chou et al, 2013 ; He et al, 2015 ; Mohd Nor et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, as a kind of beneficial active microorganisms, have been fully affirmed in immune function by generating short-chain fatty acids [33], polysaccharides [34, 35], and cell wall components (peptidoglycan and lipoteichoic acid) [36]. Previous studies indicated that Bifidobacterium regulated the components of gut microbiota.…”
Section: Introductionmentioning
confidence: 99%